The Analysis of Relationship Between Achievement Motivation, Self-Efficacy and Students Social Laziness - Purwantini Purwantini; Ika Rahayu Satyaninrum; Euis Kusumarini; Mardiati Mardiati; Antonius Rino Vanchapo (Departement of Mathematics Education, 2023)
For students, social laziness is a major issue. Social lazines is linked to a number of elements, including self-efficacy and success drive. Individuals with a high level of self-efficacy can easily complete the tasks in their work group, thus they do not free ride in their work group. The purpose of this study is to investigate experimentally the link between self-eficacy and success motivation and social lazines in students. This study employs quantitative corelational approaches. This study's population consisted of students of one school in Indonesia. The sampel size for this study was 300 students drawn from eight courses using the custer random selection approach. According to the findings of this study, self-eficacy has a strong partial link with social lazines, with a significance value of 0.000 < 0.05 and a corelation value of -0.613. Achievemen motivation has a strong partially relationship with social sloth, with a significanc value of 0.000 < 0.05 and a corelation value of -0.623. Self-eficacy and succes drive are strongly asociated with social lazines. Furthermore, the three variables have a significant relationship, with a correlation value of 0.640. As a result, there is a link between students’ self-eficacy, succs motivation, and social lazines.